Quality study of Holder pasteurization of donor human milk in a neonatal personalized nutrition unit - Sylvia Caballero Martín; Maria del Carmen Sánchez Gómez de Orgaz; Manuel Sánchez Luna (Anales de Pediatría (English Edition), 2022)
Objective: Holder pasteurization is the technique used most frequently in milk banks to minimize the risk of transmission of infectious agents. Different pasteurization devices have been described that generally use hot water or air as heat sources. In our study, we analysed the quality of pasteurization achieved with a new automated water-free pasteurizer in a neonatal personalized nutrition unit in which donated milk from mothers of infants delivered at different gestational ages and of different postnatal ages is pasteurized. Material and methods: We analysed the temperatures of different phases of pasteurization with 8 external probes distributed evenly throughout the pasteurizer. We applied the optimal range criteria established by the European Milk Bank Association (EMBA) to assess the quality of pasteurization. We also analysed the macronutrient composition of 8 samples of donor human milk of different volumes before and after automated pasteurization. Results: We did not find significant differences in the following parameters under study: time from 58 °C to 62.5 °C, duration of plateau, highest temperature during plateau and length of exposure to temperatures over 58 °C. The macronutrient analysis showed significant changes in fat content but not in protein or lactose content. Conclusions: Holder pasteurization of human milk with a water-free pasteurizer met the quality standards recommended by the European Milk Bank Association independently of the quantity of milk pasteurized in each bottle and with significant changes in the fat content but not in the protein or lactose content. Resumen: Objetivo: La pasteurización Holder es la técnica utilizada más comúnmente en bancos de leche materna para minimizar el riesgo de transmisión de agentes infecciosos. Se han descrito distintos sistemas de pasteurización, que generalmente utilizan agua o aire caliente como fuentes de calor. En el presente estudio se analizó la calidad de la pasteurización realizada con un nuevo pasteurizador automatizado en seco, en una unidad de nutrición personalizada neonatal que procesa leche materna donada de madres de lactantes nacidos a distintas edades gestacionales y de distintas edades postnatales. Material y método: Se analizó la temperatura durante las distintas fases de la pasteurización con 8 sondas externas distribuidas uniformemente por todo el pasteurizador. Se aplicaron los criterios óptimos recomendados por la Asociación Europea de Bancos de Leche (EMBA) para monitorizar la calidad de la pasteurización. También se realizó un análisis de macronutrientes en 8 frascos con distintos volúmenes de leche materna donada antes y después de su pasteurización programada. Resultados: No se objetivaron diferencias significativas en los siguientes parámetros analizados: tiempo de calentamiento de 58 °C a 62,5 °C, duración de la meseta, temperatura máxima durante la meseta y tiempo de exposición a temperaturas superiores a 58 °C. El análisis de macronutrientes reveló diferencias significativas en el contenido graso, pero no en el proteico o el de lactosa. Conclusiones: La pasteurización de leche materna mediante un pasteurizador sin agua cumplió los estándares de calidad recomendados por la Asociación Europea de Bancos de Leche (EMBA), independientemente de la cantidad de leche procesada en cada frasco y con cambios significativos en el contenido graso, pero no en contenido proteico o de lactosa.